2011
DOI: 10.1038/ki.2010.539
|View full text |Cite
|
Sign up to set email alerts
|

Low-protein diet supplemented with ketoacids reduces the severity of renal disease in 5/6 nephrectomized rats: a role for KLF15

Abstract: Dietary protein restriction is an important treatment for chronic kidney disease. Herein, we tested the effect of low-protein or low-protein plus ketoacids (KA) diet in a remnant kidney model. Rats with a remnant kidney were randomized to receive normal protein diet (22%), low-protein (6%) diet (LPD), or low-protein (5%) plus KA (1%) diet for 6 months. Protein restriction prevented proteinuria, decreased blood urea nitrogen levels, and renal lesions; however, the LPD retarded growth and decreased serum albumin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
60
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 61 publications
(63 citation statements)
references
References 38 publications
(51 reference statements)
3
60
0
Order By: Relevance
“…The identification of VLPD effects, such as reduction of sodium [9] and phosphorus intake [7], reduction of FGF23 levels [7], reduction of glomerular fibrosis for increase of Kruppel-like factor 15 [39], and reduction of proteinuria [40], can determine a decision for a randomized controlled trial aimed to strongly use VLPD in a lower degree of CKD than today [41]. …”
Section: Discussionmentioning
confidence: 99%
“…The identification of VLPD effects, such as reduction of sodium [9] and phosphorus intake [7], reduction of FGF23 levels [7], reduction of glomerular fibrosis for increase of Kruppel-like factor 15 [39], and reduction of proteinuria [40], can determine a decision for a randomized controlled trial aimed to strongly use VLPD in a lower degree of CKD than today [41]. …”
Section: Discussionmentioning
confidence: 99%
“…The protein levels of TNF-α, MCP-1 and RANTES under the different experimental conditions were determined in the cell supernatants using commercial ELISA kits (R&D Systems, Inc., Minneapolis, MN, USA) according to the manufacturer's instructions, and each protein level was normalized with the cell numbers, as previously described (17).…”
Section: Enzyme-linked Immunosorbent Assay (Elisa)mentioning
confidence: 99%
“…Our previous study indicated that KLF15, which is expressed in glomeruli and interstitium, is significantly down-regulated in the renal tissues of a 5/6 nephrectomised rat CKD model and that Klf15 -/- mice are more susceptible to renal fibrosis than wild-type mice [14]. Furthermore, our research group has reported the molecular mechanism of KLF15 in the regulation of TGF-β-induced renal fibrosis [15].…”
Section: Introductionmentioning
confidence: 99%